Design characteristics of studies on medical practice variation of caesarean section rates: a scoping review - Maarten D H Vink; Piet J G M de Bekker; Xander Koolman; Maurits W van Tulder; Ralph de Vries; Ben Willem J Mol; Eric J E van der Hijden (BMC, 2020)
Abstract Background Medical practice variation in caesarean section rates is the most studied type of practice variation in the field of obstetrics and gynaecology. This has not resulted in increased homogeneity of treatment between geographic areas or healthcare providers. Our study aim was to evaluate whether current study designs on medical practice variation of caesarean section rates were optimized to identify the unwarranted share of practice variation and could contribute to the reduction of unwarranted practice variation by meeting criteria for audit and feedback. Methods We searched PubMed, Embase, EBSCO/CINAHL and Wiley/Cochrane Library from inception to March 24th, 2020. Studies that compared the rate of caesarean sections between individuals, institutions or geographic areas were included. Study design was assessed on: selection procedure of study population, data source, case-mix correction, patient preference, aggregation level of analysis, maternal and neonatal outcome, and determinants (professional and organizational characteristics). Results A total of 284 studies were included. Most studies (64%) measured the caesarean section rate in the entire study population instead of using a sample (30%). (National) databases were most often used as information source (57%). Case-mix correction was performed in 87 studies (31%). The Robson classification was used in 20% of the studies following its endorsement by the WHO in 2015. The most common levels of aggregation were hospital level (35%) and grouped hospitals (35%) e.g. private versus public. The percentage of studies that assessed the relationship between variation in caesarean section rates and maternal outcome was 9%, neonatal outcome 19%, determinants (professional and organizational characteristics) 21% and patient preference 2%. Conclusions Study designs of practice variation in caesarean sections varied considerably, raising questions about their appropriateness. Studies focused on measuring practice variation, rather than contributing to the reduction of unwarranted practice variation. Future studies should correct for differences in patient characteristics (case-mix) and patient preference to identify unwarranted practice variation. Practice variation studies could be used for audit and feedback if results are presented at lower levels of aggregation, and appeal to intrinsic motivation of physicians, for example by including the health effects on mother and child.